Workshop “I want to hear you!”: Experience report of an extension activity on hearing for senescent older adults (Research, Society and Development, 2025)
Introduction: The population aging in Brazil requires effective strategies for promoting elderly health. Age-related hearing loss negatively impacts quality of life by hindering interpersonal communication and often leading to social isolation. Therefore, a Gerontology in Speech Language Pathology interest group developed the workshop “I Want to Hear You!” to promote auditory care and encourage the adoption of healthy hearing habits among senescent elderly individuals. Objective: To evaluate the implementation of the workshop and the elderly participants’ perceptions regarding the auditory health promotion activity. Methodology: This is an experience report on a workshop held in a parish hall in João Pessoa/PB, Brazil, in August 2024, with participation of 18 elderly individuals. The event included an educational session about hearing loss, a musical activity to stimulate auditory memory, otoscopic examinations, and clinical referrals when necessary. The evaluation data were collected through a digital questionnaire with 13 questions, applied to the participants after the workshop. Results: Of the 15 elderly participants who responded to the questionnaire, 83.7% rated the workshop as excellent, and 100% reported feeling better prepared to take care of their hearing health. The majority adopted healthy hearing habits, and 60% of those referred underwent hearing assessments. The clarity of the information, the interactive approach, and the visual resources used were unanimously well received. Conclusion: The workshop proved to be effective in promoting health and raising awareness among the elderly individuals regarding auditory care, fostering autonomy, the prevention of hearing-related complications, and improving quality of life. This initiative reinforces the importance of educational actions and university extension programs in delivering comprehensive care to the elderly population.